Primary Intramedullary Spinal Cord Lymphoma Presenting as a Cervical Ring–Enhancing Lesion in an AIDS Patient. (4th June 2018) - Bini Viotti, Julia; Doblecki, Susanne; Luca, Corneliu C; Mackrides, Nicholas; Vega, Francisco; Alcaide, Maria L
Abstract: Primary intramedullary spinal cord lymphoma (PISCL) is rare and constitutes only 1% of central nervous system lymphomas. We report a case of PISCL in a 37-year-old man with advanced AIDS. To our knowledge, only 4 cases of PISCL in the setting of HIV/AIDS have been reported in the literature. Despite treatment, prognosis remains dismal.